Setting health research priorities using the CHNRI method: III. Involving stakeholders - Sachiyo Yoshida; Kerri Wazny 2*; Simon Cousens 3; Kit Yee Chan 2,4 (Edinburgh University Global Health Society, 2016)
Setting health research priorities is a complex and value-driven process. The introduction of the Child Health and Nutrition Research Initiative (CHNRI) method has made the process of setting research priorities more transparent and inclusive, but much of the process remains in the hands of funders and researchers, as described in the previous two papers in this series. However, the value systems of numerous other important stakeholders, particularly those on the receiving end of health research products, are very rarely addressed in any process of priority setting. Inclusion of a larger and more diverse group of stakeholders in the process would result in a better reflection of the system of values of the broader community, resulting in recommendations that are more legitimate and acceptable.